PENINGKATAN HASIL BELAJAR PENDIDIKAN JASMANI DAN KESEHATAN MATERI SERVIS BAWAH MELALUI PERMAINAN BOLAVOLI MODIFIKASI PADA SISWA TUNAGRAHITA RINGANKELAS V SEKOLAH DASAR - SOEJONO PUTRO, SATRIJO (Jurnal Pendidikan Khusus, 2016)
ABSTRACT  Child of Mentally Disabled is children that has mind limitation, weaken responsiveness or often recognized with mental limitation. Education Management for child of Mentally Disabled  can be conducted pass by study of sport physical education and health were as the development effort motoric student pass by bodily education program adaptive (accommodated). Games volleyball is one of existing sport branch in physical education curriculum in school and has been taught in school begin at elementary school level till college. Optimizing child ability of Mentally Disabled in conducted service movement under volleyball is must designed particularly passed by study penjas (physical education) adaptive that either in strategy or study model, and study modification matching with student condition. Research Target this is the: for describe result improvement learnt physical education and health of service matter under passed by game volleyball modification. Research Target this is the student light Mentally Disabled class V elementary school Klampis Ngasem I Surabaya that amount to 16 Childs. Method in this research use method of class action research (PTK) where study is conducted 2 cycles, where every cycle conducted 2 times meetings. Processes of data intake are conducted with observation when study takes place that is: observation of teacher activity and student, and ability motoric child in conducting service under game volleyball. Research Result: service ability under student at cycle I meeting I value as high as 45,1 with successfulness percentage as high as 0% and at meeting II value as high as 53,3 with percentage to successfulness  as high as 12,5%. Result of teacher activity observation meeting I as high as 57,5% and meeting II as high as 65%. Result of meeting student activity I as high as 50,31% and meeting II as high as 63,44%. Research Result at cycle 2 show service ability under student at meeting I getting the value as high as 63,1 with successfulness percentage as high as 62,5% and meeting II value as high as 75,1 with successfulness percentage as high as 87,5%. Result of teacher activity observation meeting I as high as 70% and meeting II as high as 90%. Result of meeting student activity I as high as 67,50% and meeting II as high as 84,06  expressed succeed, with successfulness of level student become 87,5% with success student amount 14 students and have not yet succeeded 2 students. As a whole study result from study early cycle 1 and cycle 2 experience of significant improvement, that means student experiences of ability improvement motoric in conducting service movement under at game volleyball modified. Keyword: physical education, service volleyball